Correlation Analysis of the Halal Certification Process and Perceptions of the Cost of Halal Certification with the Intentions of Food and Beverage SMEs Actors - Sugeng Santoso; Selma Alfarisah; Ari Ana Fatmawati; Rian Ubaidillah (UIN Sunan Gunung Djati Bandung, 2021)
As one of the countries with the largest Muslim population in the world (87.18%), Indonesia has the potential to become the center of the world's halal industry. Halal certification can increase the competitiveness of MSME products, especially related to product guarantees to provide comfort, security, safety, and certainty of the availability of halal products for the public in consuming and using the product. The purpose of this study is to analyze the problems and solutions for food and beverage SMEs (Ekraf) related to the Halal Certification Process and Perceptions of Halal Certification Costs with the Actor's Intention to obtain a halal certificate. The research method uses qualitative and quantitative approaches by using primary and secondary data. The qualitative approach was carried out through FGD, webinars and participant observation with key informants and supporting informants. The quantitative approach is carried out by distributing questionnaires to 100 business actors and then processing the Pearson Product Moment correlation data. The results of the study show (i) the halal certification process (by assisting) has a very strong correlation with the perpetrator's intention and is significant, (ii) the perception of the cost of halal certification (with the cost of halal certification that gets subsidized) has a strong correlation with the perpetrator's intention and is significant, ( iii) The Halal Certification Process has a strong correlation with the perpetrators' perceived Halal Certification Costs and is significant, (iv) The Halal certification process and the perceived cost of Halal certification with the perpetrator's intention are very strong and significant. The halal certification process and the perception of the cost of halal certification, both individually and jointly, are correlated with the intentions of food and beverage creative economy actors (MSMEs). In order to achieve this goal, the synergy between central and regional stakeholders and related parties is needed.